Analysis of regional investment policy direction in the general investment plan perspective of Tanjungpinang City - Budiman, Shahril; Setyadiharja, Rendra; A. Karim, Zamzami; Junriana; Mukhlis, Suhardi (2020)
The regional government of Tanjungpinang City as regional management should be more active in creating regional competitiveness and investment in developing the potential of their respective regions. This paradigm shift in regional investment is in line with the aim of spurring synergies in various aspects in the implementation of local government with the central government, the competition that is increasingly open in this era of decentralization requires local governments to organize and organize their regions operationally in order to maximize their regional potential and gain good skills managing the market in order to attract investors, both foreign capital (PMA) and investment in the State (PMDN), the development of investment in a region or region can give birth to or create opportunities for other economic activities. With the investment road map, it will become the basis for investment policies and guidelines to attract investors to make direct investment in Indonesia and Tanjungpinang City, especially as part of development. Through this research, see how the existing conditions and how policy formulation of the development plan of Tanjungpinan City and the regional genial investment plan road map.